Characterization of the genetic variability among Caesalpinia pulcherrima (L.) Sw. (Fabaceae) plants using RAPD molecular markers - doi: 10.4025/actasciagron.v34i3.13765 - Maria Gabriela Fontanetti Rodrigues; Renata Bachin Mazzini; Kathia Fernandes Lopes Pivetta; Meire de Cássia Alves; Janete Apparecida Desidério (Acta Scientiarum. Agronomy, 2011)
The species Caesalpinia pulcherrima, which belongs to the Fabaceae family, is frequently used as a hedge or street tree in urban landscapes, parks and gardens. It flowers profusely, and the flowers, depending on the variety, may be pink, orange or yellow. As flower characteristics are essential for determining the commercial value of ornamental species, the main objective of this work was to identify polymorphisms in C. pulcherrima plants that produce flowers of different colors using RAPD molecular markers. For this study, 30 adult plants were randomly chosen on streets located in Jaboticabal city, São Paulo State, Brazil, and leaf samples were collected for DNA extraction. Among these trees, 20 have orange flowers, eight have yellow flowers and only two produce pink flowers. From the 140 tested RAPD primers, 94 primers amplified defined fragments that resulted in 246 bands, which were 100% monomorphic. Thus, a polymorphism was not detected by any of the primers tested. It was concluded that the RAPD technique is not an efficient method for detecting polymorphisms and that more specific molecular markers should be tested. Additionally, the morphological characteristic “flower color” may be controlled by several genes or by the association of them.